Behavioral Neuroscience of Drug Addiction - Self, David W.; Staley Gottschalk, Julie K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Drug addiction is a chronically relapsing mental illness involving severe motivational disturbances and loss of behavioral control leading to personal dev- tation. The disorder af?icts millions of people, often co-occurring with other mental illnesses with enormous social and economic costs to society. Several decades of research have established that drugs of abuse hijack the brain$1 (Bs natural reward substrates, and that chronic drug use causes aberrant alterations in these rewa- processing systems. Such aberrations may be demonstrated at the cellular, neu- transmitter, and regional levels of information processing using either animal models or neuroimaging in humans following chronic drug exposure. Behaviorally, these neural aberrations manifest as exaggerated, altered or dysfunctional expr- sion of learned behavioral responses related to the pursuit of drug rewards, or to environmental factors that precipitate craving and relapse during periods of drug withdrawal. Current research efforts are aimed at understanding the associative and causal relationships between these neurobiological and behavioral events, such that treatment options will ultimately employ therapeutic amelioration of neural de?cits and restoration of normal brain processing to promote efforts to abstain from further drug use. The Behavioral Neuroscience of Drug Addiction, part of the Springer series on Current Topics in Behavioral Neurosciences, contains scholarly reviews by noted experts on multiple topics from both basic and clinical neuroscience ?elds.s
Neuroplastic Alterations in the Limbic System Following Cocaine or Alcohol Exposure -- Dopamine Signaling in the Nucleus Accumbens of Animals Self-Administering Drugs of Abuse -- Amygdala Mechanisms of Pavlovian Psychostimulant Conditioning and Relapse -- Prefrontal Cortical Regulation of Drug Seeking in Animal Models of Drug Relapse -- Neural Substrates of Psychostimulant Withdrawal-Induced Anhedonia -- Sensitization Processes in Drug Addiction -- Imaging Receptor Changes in Human Drug Abusers -- Imaging Neurotransmitter Release by Drugs of Abuse -- Imaging Cognitive Deficits in Drug Abuse -- Neural Markers of Genetic Vulnerability to Drug Addiction -- The Role of Executive Control in Human Drug Addiction -- The Behavioral Economics of Drug Dependence: Towards the Consilience of Economics and Behavioral Neuroscience -- Novel Pharmacological Approaches to Drug Abuse Treatment.
Keywords: Medicine; Neurosciences; Neurochemistry; Pharmacology; Neurology; Psychiatry; Psychopharmacology; Biomedicine; Neurosciences; Neurology; Pharmacology/Toxicology.; Neurochemistry; Psychiatry; Psychopharmacology; Electronic books